Adjusting and visualizing the stability of an acyl chloride through the delocalization effect and introducing AIEgens. Issue 38 (22nd April 2022) - Liu, Lu; Wan, Qing; Gui, Chen; He, Ping; Zhao, Zujin; Wang, Zhiming; Tang, Ben Zhong
Abstract : An effective molecular design strategy is achieved to stabilize an acyl chloride by delocalization, where AIEgens endow its stability visualization via the monitoring of fluorescence variation and the activity can also be modulated by adjusting the temperature and pH. Abstract : Acyl chloride is an important functional group in acylation reactions, though its compounds are difficult to store and transport due to their high reactivity. In this research, phenanthro[9, 10- d ]imidazole is introduced into an acyl chloride agent of TPEPCl to enhance the stability via the delocalization effect. Meanwhile, rarely reported acyl chloride crystals have been achieved which could further prove its stability. The tetraphenylethylene group is also employed to visually monitor the changes of TPEPCl via fluorescent variation with the help of aggregation-induced emission (AIE) characteristics. The reactivity of TPEPCl could be stimulated by a strong alkaline solution or high temperature. Crystallography analyses of acyl TPE-PI derivatives are also discussed and the relationship between the delocalization structure and stability is determined. These findings help to stabilize, control and monitor the reactivities of active functional materials for applications.